Effect of Chelating Agent Type and Addition Amount on Heavy Metal Leaching of Fly Ash in Municipal Solid Waste Incineration - Ruan, Danian; Feng, Linlin; Zhang, Yiyang; Lao, Yunfeng (Journal of Environmental Accounting and Management, 2026)
Based on the pollution control standard of municipal solid waste incineration, the pollution characteristics of fly-ash in a domestic municipal solid waste incineration power plant were analyzed and tested. The effects of the amount of hydrated lime, the type and dosage of chelating agent and the mixture of chelating agent on the leaching concentration, alkali content and pH value of leaching solution in fly ash were studied. In this study, four kinds of chelating agents (dithiocar-bamate agents (DTC), inorganic phosphate (KOP), polyamine chelators (PCA) , diethylamine chelators (DLA)) were selected to carry out the stabilization test, and the effect of heavy metal leaching after fly ash stabilization was compared and analyzed. At the same time, the pH of heavy metal leaching solution after chelation was determined, and the heavy metal chelating agent and chelating process conditions were optimized. The test results show that controlling the alkali content of fly ash is 16 23%, which is beneficial to reduce the leaching concentration of heavy metals, under the optimal dosage of 4%, the leaching concentration of Pb, Zn and Cd in fly ash solidified by DLA, DTC and PCA can meet the emission requirements, and the treatment effect is better than that of Kop, when the dosage of hydrated lime is 10 and 12 kg/t, the leaching concentration of Pb was 0.03 and 0.025 mg/L under 4% DLA + 5% Trisodium phosphate (TPE), which were 43.7% and 45.8% lower than those under 4% DLA, which indicated that the chelating agent had good stabilization effect on Pb and Zn in fly ash, and the alkali content of fly ash also played a key role in chelating effect.